2021
DOI: 10.1186/s12903-021-01576-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inferior nasal turbinate width and concha bullosa in subjects with nasal septum deviation: a cone beam tomography study

Abstract: Background In individuals with nasal septal deviation (NSD), compensatory hypertrophy of the nasal turbinates occurs as a protective mechanism of the nasal passage from dry and cold air. NSD associated nasal turbinate hypertrophy is usually recurrent, requiring repetitive imaging. Therefore, a multiplanar imaging modality with a low radiation dose is best suited for long-term follow-up of this condition. This study aimed to evaluate the association of width of inferior turbinates and presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Based on this information it can be hypothesized that the morphological changes of the ITH may be associated with morphological changes in the mucosal lining of the maxillary sinuses. Recent studies used Cone Beam Computed tomography (CBCT), to study the thickness of the sinus mucosa and the thickness of inferior turbinates [ 6 , 7 , 8 , 9 , 10 ]. Furthermore, studies also reported that the volumes of the inferior turbinate (IT) and the status of the maxillary sinus are important indicators for physicians to evaluate the sino-nasal diseases [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this information it can be hypothesized that the morphological changes of the ITH may be associated with morphological changes in the mucosal lining of the maxillary sinuses. Recent studies used Cone Beam Computed tomography (CBCT), to study the thickness of the sinus mucosa and the thickness of inferior turbinates [ 6 , 7 , 8 , 9 , 10 ]. Furthermore, studies also reported that the volumes of the inferior turbinate (IT) and the status of the maxillary sinus are important indicators for physicians to evaluate the sino-nasal diseases [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…CBCT scans in Group 1 and 2 had no evidence on NSD when viewed from the coronal section of CBCT at the point of crista galli. In CBCT scans of Group 3 the septal deviation angle was determined by the method used by Shetty et al (2021) and Al-Rawi et al (2019) ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“… 88 CBCT imaging may be indicated in cases of concomitant sinus pathologies or concerning masses, 89 and when nasal endoscopy is contraindicated, unavailable, or when the patient is uncooperative. 90 CBCT can be used to measure the hypertrophy of nasal turbinates, 91 and specific methods have been developed for turbinates grading in patients with cleft lip and palate. 92 Since turbinate hypertrophy is often a compensatory reaction to protect the nasal passage from cold and dry air in the presence of nasal septum abnormalities, 91 orthodontic intervention with RME may be beneficial.…”
Section: Upper Airway Analysis On Cbct Scansmentioning
confidence: 99%
“… 90 CBCT can be used to measure the hypertrophy of nasal turbinates, 91 and specific methods have been developed for turbinates grading in patients with cleft lip and palate. 92 Since turbinate hypertrophy is often a compensatory reaction to protect the nasal passage from cold and dry air in the presence of nasal septum abnormalities, 91 orthodontic intervention with RME may be beneficial.…”
Section: Upper Airway Analysis On Cbct Scansmentioning
confidence: 99%